Exposure Symmetry and Volatility Transmission: A Structural Theory of Portfolio Diversification - Euis Bandawaty (UDEX Institute, 2025)
Persistent market volatility has become a structurally embedded condition of contemporary competitive environments, yet diversification research continues to conceptualize corporate scope primarily in terms of breadth, relatedness, and performance outcomes. Although prior scholarship explains how firms respond to turbulence through dynamic capabilities, governance mechanisms, and organizational learning, it under-theorizes how portfolio structure itself conditions volatility transmission. This paper develops a structural theory of portfolio diversification by introducing the construct of exposure symmetry, defined as a firm-level configuration in which volatility transmission across segments is attenuated through balanced dependency intensity, differentiated covariance structures, and capital redeployability elasticity. We argue that diversification effectiveness under persistent volatility depends not merely on scope expansion but on the architecture through which exposure is distributed and interconnected. The framework specifies three interdependent structural dimensions—exposure concentration intensity, exposure covariance structure, and structural elasticity—and advances propositions explaining how exposure architecture moderates the relationship between sustained volatility and strategic instability. By shifting attention from configurational classification toward volatility transmission mechanisms, this study extends diversification theory and clarifies the structural foundations of strategic stability under sustained turbulence.